2024
DOI: 10.3390/microorganisms12010192
|View full text |Cite
|
Sign up to set email alerts
|

The Response of the Honey Bee Gut Microbiota to Nosema ceranae Is Modulated by the Probiotic Pediococcus acidilactici and the Neonicotinoid Thiamethoxam

Thania Sbaghdi,
Julian R. Garneau,
Simon Yersin
et al.

Abstract: The honey bee Apis mellifera is exposed to a variety of biotic and abiotic stressors, such as the highly prevalent microsporidian parasite Nosema (Vairimorpha) ceranae and neonicotinoid insecticides. Both can affect honey bee physiology and microbial gut communities, eventually reducing its lifespan. They can also have a combined effect on the insect’s survival. The use of bacterial probiotics has been proposed to improve honey bee health, but their beneficial effect remains an open question. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(83 reference statements)
0
0
0
Order By: Relevance
“…Interestingly, the FB group showed marginally fewer negative interactions than the Fumidil B ® group. A recent study also showed that Bactocell ® restored the bee microbiota to a state close to the control after the induction of dysbiosis by a stressor factor ( V. ceranae ) [ 52 ]. In this context, Bactocell ® could be administrated as a complementary product to mitigate the negative impacts exerted by Fumidil ® , and possibly other antimicrobials, on bee microbiota, especially prior to wintering.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the FB group showed marginally fewer negative interactions than the Fumidil B ® group. A recent study also showed that Bactocell ® restored the bee microbiota to a state close to the control after the induction of dysbiosis by a stressor factor ( V. ceranae ) [ 52 ]. In this context, Bactocell ® could be administrated as a complementary product to mitigate the negative impacts exerted by Fumidil ® , and possibly other antimicrobials, on bee microbiota, especially prior to wintering.…”
Section: Discussionmentioning
confidence: 99%